84 Umbilical metastasis of an endometrial carcinoma: a case report. (13th November 2020) - Sá, I; Raposo, S; Sousa, R; Sá, L
Abstract : Background: Sister Mary Joseph's nodule (SMJN) can be the first manifestation of an underlying malignancy or an indication of a recurrence in a patient with a previous malignancy. The incidence is about 1–3%. The most common origin of SMJN is ovarian and gastric carcinoma and is often a sign of poor prognosis. Metastases from primary endometrial cancer to the umbilicus are rare. According to the published literature, we only count 32 cases of SMJN with endometrial origin. Results: A 77-year-old obese woman with type II diabetes and hypertension was referred to our institution for an endometrial adenocarcinoma G1 diagnosed in a previous biopsy. Total abdominal hysterectomy and bilateral salpingo-oophorectomy was performed. Histologic diagnosis revealed an endometrioid adenocarcinoma G1 with a depth of myometrial invasion <50% and negative peritoneal washing cytology - FIGO stage IA. Seven months later, the patient presented with a cutaneous nodule on the umbilical region measuring 52 mm. A skin biopsy showed metastasis of an endometrial adenocarcinoma. A CT scan did not show any other abdominal mass, ascites, regional lymphadenopathy or pulmonary lesions. A second surgery including full recession of the umbilical lesion and abdominal wall mesh repair was performed. Histological diagnosis revealed metastasis of the same origin with her primary disease with clear margins. The patient remains in clinical control in our institution. Conclusions: We presented a very rare case of umbilical metastasis(SMJN) of an endometrial adenocarcinoma. We decided to perform surgery alone, since there are not specific recommendations about other therapeutic approaches.